Commissioning and validation of a novel commercial TPS for ocular proton therapy. Issue 1 (23rd October 2022) - Wulff, Jörg; Koska, Benjamin; Heufelder, Jens; Janson, Martin; Bäcker, Claus Maximilian; Siregar, Hilda; Behrends, Carina; Bäumer, Christian; Foerster, Andreas; Bechrakis, Nikolaos E.; Timmermann, Beate
Abstract: Background: Until today, the majority of ocular proton treatments worldwide were planned with the EYEPLAN treatment planning system (TPS). Recently, the commercial, computed tomography (CT)‐based TPS for ocular proton therapy RayOcular was released, which follows the general concepts of model‐based treatment planning approach in conjunction with a pencil‐beam‐type dose algorithm (PBA). Purpose: To validate RayOcular with respect to two main features: accurate geometrical representation of the eye model and accuracy of its dose calculation algorithm in combination with an Ion Beam Applications (IBA) eye treatment delivery system. Methods: Different 3D‐printed eye‐ball‐phantoms were fabricated to test the geometrical representation of the corresponding CT‐based model, both in orthogonal 2D images for X‐ray image overlay and in fundus view overlaid with a funduscopy. For the latter, the phantom was equipped with a lens matching refraction of the human eye. Funduscopy was acquired in a Zeiss Claus 500 camera. Tantalum clips and fiducials attached to the phantoms were localized in the TPS model, and residual deviations to the actual position in X‐ray images for various orientations of the phantom were determined, after the nominal eye orientation was corrected in RayOcular to obtain a best overall fit. In the fundus view, deviations between known and displayed distances were measured. Dose calculation accuracy of the PBA on a 0.2 mm grid was investigated by comparing between measured lateral and depth–dose profiles in water for various combinations of range, modulation, and field‐size. Ultimately, the modeling of dose distributions behind wedges was tested. A 1D gamma‐test was applied, and the lateral and distal penumbra were further compared. Results: Average residuals between model clips and visible clips/fiducials in orthogonal X‐ray images were within 0.3 mm, including different orientations of the phantom. The differences between measured distances on the registered funduscopy image in the RayOcular fundus view and the known ground‐truth were within 1 mm up to 10.5 mm distance from the posterior pole. No clear benefit projection of either polar mode or camera mode could be identified, the latter mimicking camera properties. Measured dose distributions were reproduced with gamma‐test pass‐rates of >95% with 2%/0.3 mm for depth and lateral profiles in the middle of spread‐out Bragg‐peaks. Distal falloff and lateral penumbra were within 0.2 mm for fields without a wedge. For shallow depths, the agreement was worse, reaching pass‐rates down to 80% with 5%/0.3 mm when comparing lateral profiles in air. This is caused by low‐energy protons from a scatter source in the IBA system not modeled by RayOcular. Dose distributions modified by wedges were reproduced, matching the wedge‐induced broadening of the lateral penumbra to within 0.4 mm for the investigated cases and showing the excess dose within the field due to wedge scatter. Conclusion: RayOcular was validated for its use with an IBA single scattering delivery nozzle. Geometric modeling of the eye and representation of 2D projections fulfill clinical requirements. The PBA dose calculation reproduces measured distributions and allows explicit handling of wedges, overcoming approximations of simpler dose calculation algorithms used in other systems.